PRALINE: study protocol for a phase IIb inpatient stroke rehabilitation randomized controlled trial investigating longitudinal outcomes after progressive abduction loading therapy - Heidi R. Roth; Carolina Carmona; Gina Clark; Jane E. Gyarmaty; Julius P. A. Dewald; Elise Giblin; Richard L. Harvey; Jacquelyn Jaskiewicz; Kwang-Youn A. Kim; Nicola Lancki; Alexis Luhrsen; Ahalya Mandana; et al. (Trials)
Abstract Background Stroke is the leading cause of long-term disability with paucity of evidence-based interventions for individuals with severe upper extremity impairment in the affected arm. Loss of independent joint control limits reaching distance and velocity contributing to activity and participation limitations. Emerging evidence demonstrates improved independent upper extremity joint movement with training combining shoulder abduction loading during high repetition, task-specific reaching practice. The purpose of this study is to compare outcomes for one-year post-stroke for participants who receive reaching training with vs without progressive shoulder abduction loading during upper extremity reaching training using a standardized mechantronic device. Methods This is a phase II, double-blinded randomized clinical trial conducted at two inpatient rehabilitation hospitals. Eighty-six individuals will be recruited upon admission to acute inpatient rehabilitation and randomly allocated to either the experimental or active comparator intervention groups. Both groups will receive reaching training with the affected upper extremity in a standardized mechatronic device 4 days per week while in inpatient or day rehabilitation. Outcomes will be assessed at baseline, weekly while in inpatient and day rehabilitation, and every other month after discharge until one year post-stroke. Primary outcomes include change in reaching function of the affected upper extremity, measured by kinematic evaluation. This captures the loss of independent joint control due to flexion synergy expression. Secondary outcomes include measures of severity of flexion synergy motor impairment, Action Research Arm Test, Fugl-Meyer Assessment, and the Stroke Impact Scale. Discussion This study will test the efficacy of progressive shoulder abduction loading during reaching training using a mechatronic device. The results of this study have the potential to inform clinical practice for upper extremity reaching training for individuals with severe upper extremity impairment post-stroke to reduce flexion synergy expression. Trial registration Clinicaltrials.gov, NCT04118998. Registered on 8 October 2019.